Harmonization of competition laws after Doha : substantive and procedural harmonization - Takigawa, Toshiaki (2002)
Examines how and to what extent domestic competition laws should be harmonized. Distinguishes between harmonization of substantive law and harmonization of the law's procedural aspects, since the two aspects differently affect national sovereignty and are not similarly attainable.